Towards a Genuine Economic and Monetary Union—Comments on a Roadmap - Belke, Ansgar (2013)
The Van Rompuy Report and also additional proposals made by the European Commission outlined steps for a 'genuine Economic and Monetary Union'. This article explains, assesses and comments on the proposals made. Moreover, it outlines what could be recommendations in order to achieve a 'genuine Economic and Monetary Union'. For this purpose, details of the Interim Report are systematically evaluated. We also deal with different governance visions emerging from the ongoing euro area crisis and starts from different views of the 'North and the South' of the euro area on this issue. This contribution argues that there is an alternative option to the notion of cooperative fiscal federalism involving fiscal union, bailouts and debt mutualisation: competition-based fiscal federalism accompanied by a properly defined banking union. In order to be a successful one, any deal will have to come up with a successful recipe of how to (re-)create trust between European citizens and their elected governments.